Cardiac Pacemaker Dysfunction Arising From Different Studies of Ion Channel Remodeling in the Aging Rat Heart - Alghamdi, Aaazh M.; Boyett, Mark R.; Hancox, Jules C.; Zhang, Henggui (Frontiers in Physiology, 2020)
The function of the sinoatrial node (SAN), the pacemaker of the heart, declines with age, resulting in increased incidence of sinoatrial node dysfunction (SND) in older adults. The present study assesses potential ionic mechanisms underlying age associated SND. Two group studies have identified complex and various changes in some of membrane ion channels in aged rat SAN, the first group (Ageing Study-1) indicates a considerable changes of gene expression with up-regulation of mRNA in ion channels of Cav1.2, Cav1.3 and KvLQT1, Kv4.2, and the Ca2+ handling proteins of SERCA2a, and down-regulation of Cav3.1, NCX, and HCN1 and the Ca2+-clock proteins of RYR2. The second group (Ageing Study-2) suggests a different pattern of changes, including down regulation of Cav1.2, Cav1.3 and HCN4, and RYR2, and an increase of NCX and SERCA densities and proteins. Although both data sets shared a similar finding for some specific ion channels, such as down regulation of HCN4, NCX, and RYR2, there are contradictory changes for some other membrane ion channels, such as either up-regulation or down-regulation of Cav1.2, NCX and SERCA2a in aged rat SAN. The present study aims to test a hypothesis that age-related SND may arise from different ionic and molecular remodelling patterns. To test this hypothesis, a mathematical model of the electrical action potential of rat SAN myocytes was modified to simulate the functional impact of age-induced changes on membrane ion channels and intracellular Ca2+ handling as observed in Ageing Study-1 and Ageing Study-2. The role and relative importance of each individually remodelled ion channels and Ca2+-handling in the two datasets were evaluated. It was shown that the age-induced changes in ion channels and Ca2+-handling, based on either Ageing Study-1 or Ageing Study-2, produced similar bradycardic effects as manifested by a marked reduction in the heart rate (HR) that matched experimental observations. Further analysis showed that although the SND arose from an integrated action of all remodelling of ion channels and Ca2+-handling in both studies, it was the change to ICaL that played the most important influence.